CRISPR/Cas9 Systems and Gene Editing Technology - Gök, Özlem; Beyaz, Seda; Aslan, Abdullah (My University, 2023)
This review on gene editing technologies summarizes the features, applications and future of the CRISPR/Cas9 genome regulating system. Recently, the aim of searchers has been to improve cost-effective and reliable ways to perform goal modify to the genome of living cells. Thanks to the improvement of the CRISPR/Cas9 system, it has made progress in many fields such as molecular biology, biomedicine and medicine. Moreover, it has contributed to important developments in the field of genome engineering through targeted breaks in the DNA of almost every organism and cell type.
Keywords: CRISPR; Gene expression; Cas9; Genome engineering